2014
DOI: 10.1002/jsfa.6672
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptance of quality protein maize (QPM) in East Africa

Abstract: Background: Undernutrition in sub-Saharan Africa remains problematic, and quality protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…The experience of this study showed how BDM, which is conducted individually, was easy to use with respondents with little or no education, and particularly suited for rural dispersed populations. It was therefore selected to estimate WTP for quality protein maize, in combination with both central locations affective tests and modified home use tests, with adults and with both mothers and children, with all experiments including an information component.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The experience of this study showed how BDM, which is conducted individually, was easy to use with respondents with little or no education, and particularly suited for rural dispersed populations. It was therefore selected to estimate WTP for quality protein maize, in combination with both central locations affective tests and modified home use tests, with adults and with both mothers and children, with all experiments including an information component.…”
Section: Methodsmentioning
confidence: 99%
“…If the respondents are randomly selected, the standard procedure assumes that u i is randomly distributed; it is also called the random effects model. Such models have been used to analyse farmer participatory evaluation of new technologies and consumer evaluation of maize products …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The widely used 5-point hedonic scale for evaluating sensory characteristics such as color, taste, flavor and texture was used (De Groote et al, 2014). Panelists were asked to evaluate tomato sauce at each testing time session on the 5 point scale (5 = Like extremely; 4 = Like very much; 3 = Like moderately; 2 = Neither like nor dislike; 1 = Dislike).…”
Section: Sensory Evaluationmentioning
confidence: 99%